Effect of a bioactive pit and fissure sealant on demineralized human enamel: in vitro study - Rehab Samir Salma; Omnia M. AbdElfatah (BMC, 2022)
Abstract Background Incorporation of bioactive agent into pit and fissure sealant would halt demineralization and promote further remineralization. The aim was to assess the effect of bioactive and fluoride fissure sealants on calcium and phosphate content and surface topography of artificially demineralized enamel in young permanent teeth. Methods 30 sound extracted premolars free from cracks or any developmental anomalies were used. They were divided into group I bioactive fissure sealant, group II fluoride fissure sealant and group III no material applied. Each tooth was divided into halves in a buccolingual direction and evaluated by energy dispersive X-ray spectrometer (EDX) at baseline, demineralization and after applying the material. Another set of 7 sound extracted premolars was evaluated by scanning electron microscopy (SEM) at the same phases. Results EDX showed that regaining calcium to demineralized enamel was significantly higher with bioactive sealant than either fluoride or the control group. SEM revealed minerals deposits with formation of distinct white zone at tooth/sealant interface for both pit and fissure sealant groups. Whereas no white zone formation was detected in control group. Conclusions Incorporating bioactive material into pit and fissure sealant through microcapsules provided better results than incorporating fluoride by enhancing the biological process of remineralization. Clinical relevance: The more use of bioactive pit and fissure sealant would maintain the occlusal surfaces as sound structures and decrease the need for operative procedures to restore teeth cavitation.